New Insights on the Diurnal Mechanism of Calcification in the Stony Coral, Stylophora pistillata - Neder, Maayan; Saar, Raoul; Malik, Assaf; Antler, Gilad; Mass, Tali (Frontiers in Marine Science, 2022)
Scleractinian corals are evolutionary-successful calcifying marine organisms, which utilize an endo-symbiotic relationship with photosynthetic dinoflagellate algae that supply energy products to their coral hosts. This energy further supports a higher calcification rate during the day in a process known as light enhanced calcification. Although this process has been studied for decades, the mechanisms behind it are still unknown. However, photosynthesis and respiration also cause daily fluctuations in oxygen and pH levels, resulting in the coral facing highly variable conditions. Here we correlated gene expression patterns with the physiological differences along the diel cycle to provide new insights on the daily dynamic processes, including circadian rhythm, calcification, symbiosis, cellular arrangement, metabolism, and energy budget. During daytime, when solar radiation levels are highest, we observed increased calcification rate combined with an extensive up-regulation of genes associated with reactive oxygen species, redox, metabolism, ion transporters, skeletal organic matrix, and mineral formation. During the night, we observed a vast shift toward up-regulation of genes associated with cilia movement, tissue development, cellular movement, antioxidants, protein synthesis, and skeletal organic matrix formation. Our results suggest that light enhanced calcification is related to several processes that occur across the diel cycle; during nighttime, tissue might elevate away from the skeleton, extending the calcifying space area to enable the formation of a new organic framework template. During daytime, the combination of synthesis of acid-rich proteins and a greater flux of ions to the sites of calcification facilitate the conditions for extensive mineral growth.